Influencing of Work-Life Balance and Job Satisfaction on Quality of Life among Thai Professional Nurses - ถ่างกระโทก, ปราโมทย์; ไตรนาทถวัลย์, วินัย; ไชยโม, เอกกมล; ยิ่งยวด, ภราดร (Journal of Health Science of Thailand, 2021)
The aims of this descriptive study was to examine the relationship between work-life balance and job satisfaction on the quality of life among Thai professional nurses. The participants of this study consisted of 400 Thai professional nurses participated during April and July 2016. The online questionnaire were the job satisfaction, work-life balance, and quality of life of Thai professional nurse’s scale. The reliability was analyzed by Cronbach’s alpha coefficient which was 0.93, 0.94 and 0.95, respectively. Descriptive statistics, Pearson’s product moment correlation coefficient, and stepwise multiple regression analysis were employed for data analyses. The results showed that average mean score of work-life balance was low (mean=2.44, SD=0.77), and job satisfaction was low (mean=2.37, SD=0.71). The average score of quality of life of Thai professional nurses was moderate (mean=78.90 SD=16.52). The influence of work-life balance and job satisfaction was correlated with the quality of life among Thai professional nurses. The two variables could explain 27.80% of the variation in the quality of life of Thai professional nurses. (R2 =0.278, F=76.25, p<0.01) As a consequence, the executives should provide and build work-life balance and job satisfaction, in order to improve the quality of life among Thai professional nurses.